Gambaran Pelaksanaan Surveilans Demam Berdarah Dengue (DBD) di Kabupaten Sabu Raijua - Celine Mudji Wadoe; Imelda Februati Ester Manurung; Ribka Limbu (Universitas Malahayati Lampung, 2023)
ABSTRACT DHF surveillance is a process of continuously monitoring the situation of DHF and conditions that influence the increase and transmission of the disease so that control measures can be taken efficiently and effectively. This study aims to describe the implementation of DHF surveillance in Sabu Raijua District. This type of research is qualitative with in-depth interview techniques. Participants in the study were 5 surveillance officers who were taken by purposive sampling technique. The main research instrument is the researcher assisted by in-depth interview guidelines. The research results show that from the input component, there are still obstacles, namely inadequate human resources, lack of training related to DHF surveillance, and delays in disbursing funds. In the process component, there are obstacles in reporting DHF surveillance data and limitations in interpreting DHF surveillance data. The output component still needs to be considered, namely the dissemination of information is not comprehensive and the feedback received is not optimal Keywords : DHF, Surveillance System ABSTRAK Surveilans DBD adalah proses pemantauan secara terus-menerus tentang situasi DBD dan kondisi yang mempengaruhi terjadinya peningkatan dan penularan penyakit tersebut agar dapat dilakukan tindakan pengendalian secara efisien dan efektif. Penelitian ini bertujuan untuk melihat gambaran pelaksanaan surveilans DBD di Kabupaten Sabu Raijua. Jenis penelitian adalah kualitatif dengan teknik wawancara mendalam. Partisipan dalam penelitian berjumlah 5 orang petugas surveilans yang diambil dengan teknik purposive sampling. Instrumen utama penelitian adalah peneliti dibantu dengan pedoman wawancara mendalam. Hasil penelitian diketahui bahwa dari komponen input, masih ada kendala yaitu SDM yang belum memadai, belum adanya pelatihan terkait surveilans DBD, dan keterlambatan pencairan dana. Komponen proses, terdapat hambatan dalam pelaporan data surveilans DBD dan keterbatasan interpretasi data surveilans DBD. Komponen output, masih perlu diperhatikan yaitu diseminasi informasi belum menyeluruh dan belum maksimalnya umpan balik yang diterima. Kata Kunci: DBD, Sistem Surveilans